State-controlled entities as claimants in international investment arbitration: an early assessment - Michael D. Nolan; Frédéric G. Sourgens (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
State-controlled entities, including state-owned enterprises and sovereign wealth funds, are increasingly important participants in international investment flows and international trade. As claimants in contractual arbitrations, they may face some unique issues, since it is not always clear whether such disputes may be considered "commercial". Until the status of such claims has been resolved, each case has to be examined on its merits.
Keywords: 330